Stereomicroscopic study on unsectioned extracted teeth - Narayan, V. Keerthi (J Forensic Dent Sci, 2017)
INTRODUCTION: Age has been considered as a reliable marker for establishing the identity of a person in the field of forensic medicine. Teeth are useful skeletal indicators of age at death since it can survive for decades. Nondestructive methods ensure the evident preservation of dental hard tissues that reflect age changes from the cradle to the grave. Therefore, an attempt was made for estimating the age using the nondestructive method. AIMS AND OBJECTIVES: The aim of this study to assess whether physiological changes of the teeth allow possible correlation for accurate age estimation and to establish a graduation standard by microscopic observation for a better age correlation. MATERIALS AND METHODS: The study was carried on 209 teeth samples extracted for orthodontic treatment or periodontal diseases comprised both maxillary and mandibular teeth across different age groups. The assessment of these changes was carried out by well-established standard methods with some proposed modifications. RESULTS: Pearson correlation analyses revealed root dentin translucency with the highest correlation (r = 0.97) followed by periodontal ligament attachment (r = 0.95), root dentin color (r = 0.95), and attrition being the least correlated (r = 0.90). All the parameters taken for the study contributed to stepwise linear regression analysis (R = 0.98; P < 0.01) indicating a strongly positive relationship between age and the changes observed. A regression formula was obtained with mean error age difference ±1.0 years. CONCLUSION: The present study showed that extracted tooth is highly significant in identifying the age without being sectioned or further processed and also signifies the use of microscope for observation of these changes, thus reducing the errors of calibrating the age.